Agama sebagai Solidaritas Sosial: Dinamika Perlawanan Kelompok Tani Panji Perjuangan di Desa Teluk Panji, Kabupaten Labuhanbatu Selatan - Indriani Frasiska; Faisal Riza (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
This article examines the role of collective solidarity in sustaining the agrarian resistance movement of the Panji Perjuangan Farmers Group in Teluk Panji Village, South Labuhanbatu. The study departs from the prolonged agrarian conflict experienced by local farmers and investigates how social cohesion enabled the movement to survive for more than four decades. Using a qualitative method with sociological and historical approaches, data were collected through interviews, observation, documentation, and historical interpretation. The findings reveal that religious elements were not formally articulated as the ideological foundation of the movement; instead, religious values functioned as moral ethics that strengthened mutual trust, collective responsibility, and social cohesion among farmers. The study identifies concrete forms of solidarity expressed through collective land defense, communal decision-making, mutual assistance, and intergenerational commitment in maintaining resistance. This article argues that the endurance of the movement was primarily shaped by collective solidarity rooted in shared social experiences rather than formal religious mobilization. The study contributes to agrarian sociology by demonstrating that local solidarity networks remain central in sustaining long-term rural resistance movements.